Pre-injury frailty and clinical care trajectory of older adults with trauma injuries: A retrospective cohort analysis of A large level I US trauma center - Oluwaseun Adeyemi; Corita Grudzen; Charles DiMaggio; Ian Wittman; Ana Velez-Rosborough; Mauricio Arcila-Mesa; Allison Cuthel; Helen Poracky; Polina Meyman; Joshua Chodosh (PLoS ONE, 2025)
Background Pre-injury frailty among older adults with trauma injuries is a predictor of increased morbidity and mortality. Objectives We sought to determine the relationship between frailty status and the care trajectories of older adult patients who underwent frailty screening in the emergency department (ED). Methods Using a retrospective cohort design, we pooled trauma data from a single institutional trauma database from August 2020 to June 2023. We limited the data to adults 65 years and older, who had trauma injuries and frailty screening at ED presentation (N = 2,862). The predictor variable was frailty status, measured as either robust (score 0), pre-frail (score 1–2), or frail (score 3–5) using the FRAIL index. The outcome variables were measures of clinical care trajectory: trauma team activation, inpatient admission, ED discharge, length of hospital stay, in-hospital death, home discharge, and discharge to rehabilitation. We controlled for age, sex, race/ethnicity, health insurance type, body mass index, Charlson Comorbidity Index, injury type and severity, and Glasgow Coma Scale score. We performed multivariable logistic and quantile regressions to measure the influence of frailty on post-trauma care trajectories. Results The mean (SD) age of the study population was 80 (8.9) years, and the population was predominantly female (64%) and non-Hispanic White (60%). Compared to those classified as robust, those categorized as frail had 2.5 (95% CI: 1.86–3.23), 3.1 (95% CI: 2.28–4.12), and 0.3 (95% CI: 0.23–0.42) times the adjusted odds of trauma team activation, inpatient admission, and ED discharge, respectively. Also, those classified as frail had significantly longer lengths of hospital stay as well as 3.7 (1.07–12.62), 0.4 (0.28–0.47), and 2.2 (95% CI: 1.71–2.91) times the odds of in-hospital death, home discharge, and discharge to rehabilitation, respectively. Conclusion Pre-injury frailty is a predictor of clinical care trajectories for older adults with trauma injuries.